Primary Implant Stability: A Crucial Pillar in Implantology (Academia Journal of Medicine, 2024)
A good implant integration and long-term favourable  clinical outcome are positively correlated with a secure  primary (mechanical) stability of the implant.  Consequently, in order to guarantee a successful  osseointegration, it is crucial to evaluate the initial stability  at various time points. This review explores the importance  of the primary and secondary implant stability and various  tools and instruments to measure the primary implant  stability, and also explains about factors affecting the  implant primary stability. Dental implant design and its  length, diameter, thread depth plays an important role in  obtaining the primary implant stability.This review  describes different ways to obtain primary stability in  compromised bone such aslow density bone and  regenerated bone.
Keywords: Implant stability; primary stability; RFA; bone density